The Cinnamon Bun Book Store - Gilmore, Laurie (Gilmore, Laurie. Dream Harbor series, 2024)
When a secret message turns up hidden in a book in the Cinnamon Bun Book Store, Hazel can't understand it. As more secret codes appear between the pages, she decides to follow the trail of clues. She just need someone to help her out. Gorgeous and outgoing fisherman, Noah, is always up for an adventure. And a scavenger hunt sounds like a lot of fun. Even better that the cute bookseller he's been crushing on for months is the one who wants his help! Hazel didn't go looking for romance, but as the treasure hunt leads her and Noah around Dream Harbor, their undeniable chemistry might be just as hot as the fresh-out-of-the-oven cinnamon buns the bookstore sells.